Pengaruh Bahan Mineral dan Air Laut terhadap Sifat Fisika – Kimia Tanah dan Pertumbuhan Padi di Lahan Gambut Dataran Tinggi - Jul Bahori Panggabean; Sarifuddin Sarifuddin; Mariani Mariani Br. Sembiring (Universitas Sumatera Utara, 2014)
Objective of this research is studied of mineral substances and sea water effect on physico-chemicalproperties of highland peat. It was conducted at highland peat in Hutabagasan, Dolok SanggulSub – district Humbang Hasundutan Regency, North Sumatera. This research used non – factorialrandomized block design with four treatments those are G0 (Control), G1 (5kgs Volcanic sand), G2(5kgs Volcanic sand + 2,5L Sea water), G3 (5kgs Volcanic sand + 1kg Zeolite + 2,5L Sea water)and 3 replicants. The results showed that application of Volcanic sand (G1) significantly increasingon soil base saturation. Addition of sea water with volcanic sand and volcanic sand + zeolite (G2dan G3) significantly increasing on soil electric conductivity, exchangeable sodium, exchangeablemagnesium but decrease exchangeable calsium, and base saturation. Zeolite has a role as buffer ofsoil pH, soil electric conductivity and bulk dencity. The Application of all ameliorants have notpositive influence on the growth of rice plant and even decrease number of vegetative tillers.Keyword: Volcanic sand, Zeolite, Sea water, Highland Peat soil, Rice.